Content Analyses of Scientific Articles Published in Sport Mont Journal Year 2007 - Boris Banjevic (Journal of Anthropology of Sport and Physical Education)
Sport Mont is a scientifi c journal which has been existing since 2003 and it has published a great number of works of renowned scientists in the fi eld of sport sciences and medicine. The journal has been indexed in more international database, it is released three times a year, and the published works are mostly presented on the scientifi c conference of the Montenegrin Sport Academy. Sport Mont, in addition to the original scientifi c works, publishes reviews, editorials, short reports, as well as the calls and awards for works in the fi eld of sport sciences and medicine. This work deals with the analysis of the content of published articles in the journal Sport Mont in 2007. They have been sorted according to the scientifi c fi elds they belong to, and through discussion, a short overview of the obtained results has been given. This way makes possible an easier search of the mentioned articles for the authors who express their interest for them.